The death of Jacob : narrative conventions in Genesis 47.28-50.26 - Lee, Kerry D. (Biblical Interpretation Series, 2015)
In The Death of Jacob: Narrative Conventions in Genesis 47.28-50.26 Kerry Lee investigates the deathbed story of the patriarch Jacob and uncovers the presence of a variety of conventional structures underlying its composition, especially a conventional deathbed story or type scene also found in numerous other texts in the Hebrew Bible and non-canonical Jewish literature. Finding fault both with traditional diachronic approaches as well as more recent synchronic studies, Lee uses an eclectic but coherent blend of contemporary methods (drawn from narratology, linguistics, ritual theory, legal theory, assyriology, and other disciplines) to show that despite its probably composite pre-history the last three chapters of Genesis have been intentionally and artfully structured by the hand predominately responsible for their final form.